Elliptical Split Ring Structure Reconfigurable Antenna for Advance Communication - Dwivedi S. (My University, 2025)
Elliptical split ring resonator structure antenna has been proposed to get frequency reconfigurability in order to use for different applications. There are several other structures that have already been used to achieve the reconfigurability having complex structures compared to this structure. In this design, bottom and middle layers are made of metal with same design parameters. Also, middle layer is made of dielectric between ground and patch. Here, probe feeding is being used to excite the antenna. To achieve reconfiguration properties, two PIN diodes have been used which are acting as a switch. By using these switches, four gains have been obtained at four different frequencies which represent the frequency reconfiguration property in designed antenna. Top layer is made up of metamaterial in which elliptical split ring resonator structure is being used. All the design has been done using CST microwave studio. Here, reflection coefficient has been achieved less than − 10 dB and VSWR less than 2. All four gains are 2.66 dBi, 2.76 dBi, 2.78 dBi, and 2.67 dBi at 9.91 GHz, 9.94 GHz, 10.27 GHz, and 10.14 GHz respectively. This design is useful for beam steering and phase array to locate the target, etc. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.